Analisis Kepuasan Pengguna Terhadap Penerapan Rekam Medis Elektronik Menggunakan Metode EUCS di RSUD Kota Salatiga - Maria Ervina Damaranti; Wahyu Ratri Sukmaningsih; Aries Widiyoko (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2026)
System convenience, data access speed, and reliability greatly affect RME user satisfaction. Salatiga City Hospital has been using RME, but there are still some issues that need to be addressed, such as unstable network, double data entry, and complicated flow. This leads to longer queues and longer patient waiting times. By applying the End User Computing Satisfaction (EUCS) method, which includes 5 dimensions: content, accuracy, format, timeliness, and ease of use, the purpose of this study was to measure user satisfaction with RME. The type of research used was quantitative analytical with a cross sectional approach. Purposive sampling was used to select the sample, which included 50 respondents who met the requirements for inclusion. The instrument applied was a questionnaire distributed to outpatient unit officers who used RME, with answers provided. Univariate and bivariate tests were used to analyse the data. The study results proved that there was a significant correlation between electronic medical record user satisfaction and the variables of content (0.000), accuracy (0.002), format (0.001), timeliness (0.000), and ease of use (0.000). As a result, improvements in these aspects are essential to increase user satisfaction and the effectiveness of the RME system in hospitals.